2007
DOI: 10.21608/mjfmct.2007.52485
|View full text |Cite
|
Sign up to set email alerts
|

Orthopantomography and Age Determination Using Third Molar Mineralization in A Sample of Egyptians

Abstract: In the last decade, the number of unidentified cadavers and cases lacking age documentation and therefore requiring age determination has increased. Dental age determination still represents today the most sensitive mean. In the age span of 15-26 years of age the wisdom teeth represent the only teeth still in development and thereby very important for dental age assessment. So, the aim of the present investigation was to detect the chronological age of an individual based on the dental developmental stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
2
2
0
6
Order By: Relevance
“…(24) Regarding gender differences in this stage, the mandibular third molars in females began stage H at 20.9 years which was earlier than males in contrast to Sujatha et al (17) who reported that males reached this stage earlier than females. Khosronejad et al (18) and Hassan and Abo Hamilla (25) supported the findings of the current study when the Iranian females reached certain third molar mineralization stages (only the H stage) sooner than males and in Egyptian females, all third molars reached H stage earlier than males. It becomes clear from the mean ages in both arches that at stages A-F, the subjects were probably below 18 and at stage G and H, the individuals were above 18 years; this comes in agreement with Jung and Cho (22) who reported that Korean population exhibited stage G at age of 18 years or older, and Khosronejad et al (18) who found that both G and H stages could indicate that the person might be above 18 years old.…”
Section: Discussionsupporting
confidence: 91%
“…(24) Regarding gender differences in this stage, the mandibular third molars in females began stage H at 20.9 years which was earlier than males in contrast to Sujatha et al (17) who reported that males reached this stage earlier than females. Khosronejad et al (18) and Hassan and Abo Hamilla (25) supported the findings of the current study when the Iranian females reached certain third molar mineralization stages (only the H stage) sooner than males and in Egyptian females, all third molars reached H stage earlier than males. It becomes clear from the mean ages in both arches that at stages A-F, the subjects were probably below 18 and at stage G and H, the individuals were above 18 years; this comes in agreement with Jung and Cho (22) who reported that Korean population exhibited stage G at age of 18 years or older, and Khosronejad et al (18) who found that both G and H stages could indicate that the person might be above 18 years old.…”
Section: Discussionsupporting
confidence: 91%
“…Algunos estudios van enfocados principalmente a estimar la mayoría de edad, entonces sus muestras se encuentra aproximadamente en el rango entre los 14 y 25 años (2,12,14,17,19,22,23,25,26,30,32). Otros registran desde los inicios de la mineralización del tercer molar, por lo que el límite inferior se encuentra aproximadamente a los siete años de edad (16,20,21,24,27,29,32) (Tabla 5).…”
Section: Discussionunclassified
“…En gran parte de los países, los 18 años marca la edad adulta o mayoría de edad y las implicancias legales cambian signifi cativamente, es por ello que recientemente, la cronología del desarrollo del tercer molar se ha utilizado para juzgar si una persona es un menor de edad o un adulto (17,19,22). Es importante mencionar que varios estudios han indicado que existen variaciones de acuerdo al grupo poblacional, país o etnia (12)(13)(14)(15)(16)(17)(18)(19)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionunclassified
“…The specimens belong to dental adult individuals of known sex. Full eruption of the third molar was used to estimate age class (Bolter and Zihlman, ; Hassan and Mansoura, ). The specimens of P. troglodytes are available from the online database of the Primate Research Institute at Kyoto University (KUPRI, Kyoto, Japan), from the primate skeletal collection of the National Museum of Natural History (NMNH, Washington, US), from the Senckenberg Research Institute (Frankfurt, Germany), and from the online database Morphosource (http://www.morphosource.org) at Duke University (Durham, US).…”
Section: Methodsmentioning
confidence: 99%